THE EFFECT OF MOTIVATION ON EMPLOYEE PERFORMANCE (A STUDY OF EMPLOYEES OF PDAM TIRTAMARTA IN YOGYAKARTA CITY) - Burhanudin - Burhanudin (Mega Aktiva, 2020)
This research aimed to determine the effect of the need for achievement on employee performance, the effect of the need for affiliation on employee performance, and the effect of the need for power on employee performance. The sample size used in this study was 64 employees of PDAM Tirtamarta in Yogyakarta City. The data analysis technique used multiple linear regression. The study results showed that the need for achievement has no effect on employee performance, the need for affiliation has no effect on employee performance, and the need for power have an effect on employee performance.